Pharmacogenetic testing in optimization of treatment with statins - Hiljadnikova-Bajro, Marija (My University, 2018)
Statins are a class of drugs that have been widely prescribed nowadays for treating hypercholesterolemia and thus prevent the risk of atherosclerotic cardiovascular events and consecutive mortality. Unfortunate ly, the patient’s compliance with treatment is frequently compromised by the high incidence of adverse effects including hepatotoxicity, myotoxicity, increased risk for diabetes mellitus etc. The expansion of the precision medicine concept in pharmacology has introduced pharmacogenetic testing as a potential predictive strategy in statins pharmacotherapy. A thorough literature survey was performed using the PubMed database on the published data in English language in the period 2000-2017, regarding genotype-phenotype associations in statin-induced toxicity, identifying a growing body of evidence supporting the need for pharmacogenetic approach in treatment with statins. Polymorphisms in the genes coding for the CYP450 enzymes: CYP2D6, DYP2D9, CYP3A4 and drug transporter genes like ABCB1, ABCG2 and SLCO1B1 appear to be responsible for the variable re sponse and toxicity of statins. But, many studies highlight the importance of drug interactions and epi genetics in modifying the response towards this class of drugs metabolized via pathways shared by the majority of pharmaceutical agents. With the rapid development of molecular techniques accompanied by a dramatic cost reduction in genetic testing, it can be easily anticipated that pharmacogenetic patient profiling will soon become standard of care in designing the optimal statin treatment either as a monotherapy or in combination with other phar maceuticals.
Keywords: pharmacogeentics, statins, polymorphisms, drug trasporter genes, CYP450 genes